KONSEP PEMBELAJARAN BERDIFERENSIASI PERSPEKTIF AL-QUR’AN DAN HADIS - Sya'diyah, Cholufatus; Fauji, Imam (As-Sulthan Journal of Education, 2024)
The Merdeka Curriculum is a form of implementation of Ki Hajar Dewantara's student-centered learning philosophy. One of the characteristics of the Merdeka Curriculum is understanding the needs and position of students so that they can provide learning with a portion that suits the needs of students. The curriculum applies the concept of learning differentiation, which is an effort to bridge the different characteristics of students. The purpose of this study is to analyze the verses of the Qur'an and Hadith that are in line with the concept and implementation of differentiated learning. This research uses a literature review. The result is that the concept and implementation of differentiated learning has also been reported by Allah SWT through verses in the Qur'an and practiced by Rosulloh SAW in his hadith about the most important practice.